Modern Mormonism myths and realities - Millet, Robert L. 1947- (Salt Lake City Greg Kofford Books, 2011)
Robert L. Millet provides important clarifications for Latter-day Saints about eleven of the most frequent myths used to discredit the Church. He also models how to conduct such a Bible based discussion respectfully, illustrated with his personal experiences growing up in a non-Mormons community, speaking with others of different faiths, and working with his students at Brigham Young University
A finite God -- Not Christian -- Contradicting the Bible -- Feelings, not facts -- Disdain for other churches -- Denying the Fall -- Ignoring the cross -- Works righteousness -- Universal salvation -- Usurping the divine throne -- No eternal security -- Retrospect and prospect.
Includes index and bibliographical references
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Church of Jesus Christ of Latter-day Saints -- Apologetic works; Mormon Church -- Apologetic works; Mormons